Linked open data to represent multilingual poetry collections : A proposal to solve interoperability issues between poetic repertoires - Rio Riande, María Gimena del (2016)
This paper describes the creation of a poetic ontology in order to use it as a basis to link different databases and projects working on metrics and poetry. It has been built on the model of the Spanish digital repertoire ReMetCa, but its aim is to be enlarged and improved in order to fit under every poetic system. The conceptual semantic model, written in OWL, includes classes and metadata from standard ontological models related to humanities fields (such as CIDOC or Dublin Core), and adds specific elements and properties to describe poetic phenomena. Its final objective is to interconnect, reuse and locate data disseminated through poetic repertoires, in order to boost interoperability among them.